(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Adenoidectomy is currently considered the treatment of choice for children with severe symptoms caused by Adenoids Hypertrophy (AH). Non-surgical alternative treatment options are considered in less severe cases to avoid the untoward effect of surgery. This study was aimed to evaluate the efficacy and safety of Mometasone Furoate nasal spray combined with Montelukast Sodium in children with AH. Materials and methods: This trial included 118 patients aged 3 to 13 years having symptomatic AH from the OPD of Otolaryngology and Head Neck Surgery of CMCH from May 2019 to April 2020. They were allocated to either Mometasone Furoate nasal spray combined with Montelukast Sodium (Group A: 59) or Mometasone Furoate nasal spray alone (Group B: 59) randomly for 8 weeks. Outcome measures were changes in the severity of symptoms and changes in the adenoid size from baseline. Out of 118 enrolled children, 109 children completed the study per protocol. Results: The mean total clinical symptom score before and after treatment in group A was respectively 10.04 (±1.78) and 4.92 (±1.65). In group B the corresponding figures were respectively 9.42 (±1.33) and 5.48 (±1.36). Clinical symptom scores as well as Adenoidalnasopharyngeal ratio dropped significantly in both groups without any statistical significance between two groups with 8 weeks of treatment. Conclusion: Mometasone Furoate nasal spray with and without oral Montelukast Sodium showed similar efficacy in symptom alleviation and adenoid size reduction without any superiority of combination therapy. JCMCTA 2021 ; 32 (2) : 59-63